Study Description of Children Motoric Assessment for Students with Intelektual Disabilities as a Predictor of Self-Help Development Abilities - Sumirat, Anita; Irawan, Asep Rudi (JASSI ANAKKU, 2021)
This research is motivated by a student with intellectual disabilities who have difficulty in the ability to develop themselves in wearing and folding clothes. This study will have an impact on activities of daily life. The purpose of this study was to develop a self-development program in improving motor skills in students with intellectual disabilities. The research subjects were three 9-year-old students with intellectual disabilities who had difficulties in self-development skills. The research method used is qualitative using descriptive analysis method. The results showed that the three students were able to achieve fine motor and gross motor indicators completely. The results of this study are self-development programs to wear and fold clothes in improving the motor skills of the student with intellectual disabilities. The results of the implementation test showed a change in the child's objective condition, an increase in motor skills. With the right and effective self-development program, it is hoped that it can help students with intellectual disabilities in their daily lives.